Sociocultural determinants of health and illness: a theoretical inquiry - Vivien, Yew Wong Chin; Mohd Noor, Noor Azlan (Universiti Kebangsaan Malaysia (UKM), 2014)
This article articulates the hypothesis that people do not perceive health as a single dimensional phenomenon of a physical absence of disease. In contrast, health can be determined by multi-dimensional factors that include people’s lifestyle, their perception of health and illness, and their health-seeking behaviour. By exploring available literature it highlights some of the studies which have generated mixed results and describes various social and cultural factors learnt across the research processes including the evidence that effective communication between doctors and patients can improve health outcomes such as patient satisfaction, patient adherence to treatment, and disease outcomes. Social support generally shows a favourable impact on the maintenance of health and coping with stress and illness. Patients who obtained social support from family members and friends were found to be more cooperative with their attending doctors and nurses in learning about their future and in understanding the meaning of life. Keywords: health, illness, sociocultural determinants, socioeconomic position, social support, stress